Discurso y praxis contra el fraude : consideraciones sobre la política reformista de Roberto M. Ortiz (1938-1940) - López, Ignacio Alejandro (2011)
Fil: López, Ignacio Alejandro. Pontificia Universidad Católica Argentina; Argentina